Assessing behaviour of osteoblastic cells in dynamic culture conditions using titanium-doped phosphate glass microcarriers. (February 2019) - De Silva Thompson, David; Peticone, Carlotta; Burova, Iva; Shipley, Rebecca J; Knowles, Jonathan C; Kim, Hae-Won; Micheletti, Martina; Wall, Ivan B
Tissue engineering is a promising approach for bone regeneration; yet challenges remain that limit successful translation to patients. It is necessary to understand how real-world manufacturing processes will affect the constituent cells and biomaterials that are needed to create engineered bone. Bioactive phosphate glasses processed into microspheres are an attractive platform for expanding bone-forming cells and also for driving their osteogenic differentiation and maturation. The aim of this study was to assess whether Ti-doped phosphate glass microspheres could support osteoblastic cell responses in dynamic cell culture environments. Dynamic culture conditions were achieved using microwell studies under orbital agitation. Dimensionless parameters such as the Froude number were used to inform the choice of agitation speeds, and the impact on cell proliferation and microunit formation was quantified. We found that phosphate glass microspheres doped with titanium dioxide at both 5 and 7 mol% provided a suitable biomaterial platform for effective culture of MG63 osteoblastic cells and was not cytotoxic. Dynamic culture conditions supported expansion of MG63 cells and both 150 and 300 rpm orbital shake resulted in higher cell yield than static cultures at the end of the culture (day 13). The Froude number analysis provided insight into how the microunit size could be manipulated to enable an appropriate agitation speed to be used, while ensuring buoyancy of the microunits. These small-scale experiments and analyses provide understanding of the impact of fluid flow on cell expansion that will have increasing importance when scaling up to process technologies that can deliver clinical quantities of cell-microsphere units. Such knowledge will enable future engineering of living bone-like material using processing systems such as bioreactors that use mixing and agitation for nutrient transfer, therefore introducing cells to dynamic culture conditions.